Covalent attachment of flavin adenine dinucleotide (FAD) and flavin mononucleotide (FMN) to enzymes: the current state of affairs. - Mewies, M. (Cold Spring Harbor Laboratory Press, 1998)
The first identified covalent flavoprotein, a component of mammalian succinate dehydrogenase, was reported 42 years ago. Since that time, more than 20 covalent flavoenzymes have been described, each possessing one of five modes of FAD or FMN linkage to protein. Despite the early identification of covalent flavoproteins, the mechanisms of covalent bond formation and the roles of the covalent links are only recently being appreciated. The main focus of this review is, therefore, one of mechanism and function, in addition to surveying the types of linkage observed and the methods employed for their identification. Case studies are presented for a variety of covalent flavoenzymes, from which general findings are beginning to emerge.